1995
DOI: 10.1093/ptj/75.5.426
|View full text |Cite
|
Sign up to set email alerts
|

Ergogenic Aids

Abstract: In the context of sport, an ergogenic aid can be broadly defined as a technique or substance used for the purpose of enhancing performance. Ergogenic aids have been classified as nutritional, pharmacologic, physiologic, or psychologic and range from use of accepted techniques such as carbohydrate loading to illegal and unsafe approaches such as anabolic-androgenic steroid use. The efficacy of many of these techniques is controversial, whereas the deleterious side effects are clear. The purpose of this article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
49

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 0 publications
0
35
0
49
Order By: Relevance
“…
Caffeine (1,3,7-trimethylxantine) is the most commonly consumed social drug in western society for increased physical and cognitive performance [1][2][3][4][5], and it is the main ergogenic resource used by athletes [6]. Initially controversial, caffeine was banned by the International Olympic Committee from 1980-2003 [1,6,7], but then in 2004 its use was approved by the World Anti-doping Agency (WADA), and later this year by the U.S. Anti-doping Agency (USADA; 2016).
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
Caffeine (1,3,7-trimethylxantine) is the most commonly consumed social drug in western society for increased physical and cognitive performance [1][2][3][4][5], and it is the main ergogenic resource used by athletes [6]. Initially controversial, caffeine was banned by the International Olympic Committee from 1980-2003 [1,6,7], but then in 2004 its use was approved by the World Anti-doping Agency (WADA), and later this year by the U.S. Anti-doping Agency (USADA; 2016).
…”
mentioning
confidence: 99%
“…Ergogenic doses of caffeine ranging from 3 to 9 mg/kg body mass [6] appear to have no adverse effects. A moderate oral dose of 6 mg/ kg body mass, which elicits peak plasma levels of about 60 µmol/L concentrations after 30 to 60 min, with half-life for elimination range between 2.5-10 h, is known to enhance physical and cognitive performance [5,6,10,14,15]. Blood levels of 1 -2 mmol/L are known to be toxic and even lethal [14], and have been associated with suicides [16].…”
mentioning
confidence: 99%
“…Alguns autores citam que a descoberta de que o uso de hormônios androgênicos poderiam melhorar o desempenho físico ocorreu apenas em 1939 (Thein et al, 1995;Ghaphery, 1995;Scott et al, 1996). Entretanto, Kuhn (2002) relata que tal fato teria ocorrido antes, já em 1896, quando um contemporâneo de Brown-Séquard, após autoadministrar um extrato testicular observou aumento na força muscular do seu dedo.…”
Section: Perspectivas Históricas Da Relação Entre Os Eaa E a Prática unclassified
“…While some of these aids have been shown to effect performance when used in specific situations, others remain controversial 5) . It has been suggested that the placebo effect plays a major role in the benefits claimed for some ergogenic aids 6) .…”
Section: Introductionmentioning
confidence: 99%